Sosialisasi Pelayanan Darah PMI Kota Batam Bersama Mitra Rumah Sakit/BDRS/Klinik - Novia Novia; Alif Rahman Habibi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Indonesian Red Cross (PMI) is a humanitarian organization that plays an important role in blood services in Indonesia. As an institution responsible for providing safe, quality, and affordable blood, PMI continues to strive to increase public awareness of the importance of blood donation and the services available at the Blood Donor Unit. In order to increase public awareness and participation in the importance of blood donation, the Indonesian Red Cross (PMI) implements various informative, educational, and participatory socialization methods. These methods are designed to reach various levels of society effectively and sustainably. The blood service socialization activities organized by the Indonesian Red Cross (PMI) showed positive results in terms of increasing public knowledge and participation. These activities were carried out through several methods, such as direct counseling, social media campaigns, installation of outdoor media, and collaboration with educational institutions and local communities. With increasing public knowledge about blood services, it is hoped that a community of regular and sustainable voluntary blood donors will be created, in accordance with the humanitarian principles upheld by PMI. The success of this program is highly dependent on consistency, appropriate delivery methods, and support from various elements, both government, private, and local communities.